Left Bundle Branch Area Pacing versus Right Ventricular Pacing in Patients with Atrioventricular Block: An Observational Cohort Study - Zhongxiu Chen; Yuanning Xu; Lingyun Jiang; Ran Zhang; Hongsen Zhao; Ran Liu; Lei Zhang; Yajiao Li; Xingbin Liu (Cardiovascular Therapeutics)
Objective. We aim to conduct a comparison of the safety and effectiveness performance between left bundle branch area pacing (LBBAP) and right ventricular pacing (RVP) regimens for patients with atrioventricular block (AVB). Methods. This observational cohort study included patients who underwent pacemaker implantations with LBBAP or RVP for AVB indications from the 1st of January 2018 to the 18th of November 2021 at West China Hospital. The primary composite outcome included all-cause mortality, lead failure, or heart failure hospitalization (HFH). The secondary outcome included periprocedure complication, cardiac death, or recurrent unexplained syncope. A 1 : 1 propensity score–matched cohort was conducted for left ventricular (LV) function analysis. Results. A total of 903 patients met the inclusion criteria and completed clinical follow-up. After adjusting for the possible confounders, LBBAP was independently associated with a lower risk of the primary outcome (OR 0.48, 95% CI 0.28 to 0.83, p=0.009), including a lower risk of all-cause mortality and HFH. No significant difference in the secondary outcome was detected between the groups except that LBBAP was independently associated with a lower risk of recurrent unexplained syncope. In the propensity-score matching cohort of echocardiographic analysis, the LV systolic dyssynchrony index was lower in LBBAP compared with that in RVP (5.68±1.92 vs. 6.50±2.28%, p=0.012). Conclusions. Compared to conventional RVP, LBBAP is a feasible novel pacing model associated with a significant reduction in the primary composite outcome. Moreover, LBBAP significantly reduces the risk of recurrent unexplained syncope and improves LV systolic synchrony. This study is registered with ClinicalTrials.gov NCT05722379.